Application of earned value based metrics on small-scale construction projects - Avlijaš, Radoslav; Avlijaš, Goran; Heleta, Milenko (The European Journal of Applied Economics, 2015)
The application of earned value based metrics in Serbia lags significantly behind other developed economies, regardless of the fact that is has proven to be a very useful and flexible tool for prediction of total cost and time of construction projects. This paper aims to contribute to the wider use of earned value management (EVM) as a practical metrics that can be used to track performance of small-scale construction projects. Literature review reveals how the method evolved as a fundamental tool for construction projects monitoring and refers to specific issues concerning its implementation. In order to enable practitioners to realize all advantages of earned value based performance monitoring of small-scale construction projects, the applicability of such methodology is demonstrated through a case study.